2023
DOI: 10.3390/jcm12072507
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Conservative Therapy of Adolescent Idiopathic Scoliosis (AIS) with Chêneau-Brace

Abstract: Chêneau-brace (C-Brace) is a potential tool for the treatment of adolescent idiopathic scoliosis (AIS) with a Cobb angle between 20° and 45° for the primary curve. The aim of the present study was (1) to estimate study cohorts with C-brace therapy success and therapy failure and (2) to analyze possible factors that influence the therapy outcome. Seventy-eight patients with AIS were assessed before the initiation of C-brace treatment. Each patient underwent radiography examinations before the brace, in-brace, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The conservative treatment by means of physiotherapy [5] and Cheneau-brace [6][7][8] application can be useful for the prevention of scoliotic curve progression and sometimes slows down or limits progression in patients with IS. However, many factors influence the effect of such a therapy, and the surgical implantation of deformity corrective instrumentation is necessary in the majority of progressive IS cases [9], especially when its lateral main angle exceeds 40 degrees [10].…”
Section: Introductionmentioning
confidence: 99%
“…The conservative treatment by means of physiotherapy [5] and Cheneau-brace [6][7][8] application can be useful for the prevention of scoliotic curve progression and sometimes slows down or limits progression in patients with IS. However, many factors influence the effect of such a therapy, and the surgical implantation of deformity corrective instrumentation is necessary in the majority of progressive IS cases [9], especially when its lateral main angle exceeds 40 degrees [10].…”
Section: Introductionmentioning
confidence: 99%
“…Secondarily, disorders in the conduction of neural impulses within the spinal roots, development of neuropathy in the peripheral nervous system, and neurogenic changes in the muscular system occur [1,2]. Kinesiotherapeutic treatment [3,4] and bracing [5][6][7][8] for improving the proper body posture, in the majority of IS patients provide only partial benefits for slowing down the progression of the pathological curvature. Negrini et al [9,10] concluded on the necessity for surgical intervention in IS patients with a primary Cobb angle of 40-45 degrees when a fast worsening of the pathology is expected.…”
Section: The Long-term Effects Of Improving the Motor Neural Transmis...mentioning
confidence: 99%
“…In the majority of IS patients, kinesiotherapeutic treatment [8,9] and bracing [10][11][12][13] for improving their body posture provide only partial benefits for slowing down the progression of the pathological curvature. Negrini et al [14,15] concluded the necessity for surgical intervention in IS patients with a primary Cobb angle of 40-45 degrees, where a fast worsening of the pathology is expected.…”
Section: Introductionmentioning
confidence: 99%